2006
DOI: 10.2166/wst.2006.547
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter release in low temperature thermal treatment of biological sludge for reduction of excess sludge production

Abstract: Thermal treatment applied in association with a biological system allows for a significant reduction in excess sludge production (approximately 50%). In general, heat treatment is described as a sludge disintegration technique. This paper offers a thorough study on the impact of heat treatment, at temperatures below 100 degrees C, on the solubilisation of the sludge COD and its biodegradability. Discontinuous heating experiments were performed on activated and digested sludge. At all temperatures tested the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…These results are in agreement with previous studies which reported that matter and COD solubilization increased with temperature, but treatment time had little effect if it exceeds 30 min in a temperature range of 60-190°C [24]. Similarly, in another study [25], sludge COD solubilization rate dramatically decreased after 30 min of thermal treatment.…”
Section: Application Of Fcm To Determine Cell Number In Activated Sludgesupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with previous studies which reported that matter and COD solubilization increased with temperature, but treatment time had little effect if it exceeds 30 min in a temperature range of 60-190°C [24]. Similarly, in another study [25], sludge COD solubilization rate dramatically decreased after 30 min of thermal treatment.…”
Section: Application Of Fcm To Determine Cell Number In Activated Sludgesupporting
confidence: 92%
“…The relation between cell lysis and organic matter solubilization implies that the origin of the released organic matter during the thermal treatment was mainly intracellular. This hypothesis is in accordance with Paul et al [25] who concluded that a thermal treatment below 100°C allowed only partial floc sludge destruction. These treatment conditions should be sufficient to break the non-covalent links and modify the sludge structure, but are insufficient to allow a complete floc destruction.…”
Section: Application Of Fcm To Determine Cell Number In Activated Sludgesupporting
confidence: 92%
“…This result confirmed the interest of the use of ozone pretreatment [22,28,31,50]. The values of TSS removal improvement (71% and 78.5%) are above the values proposed by Paul et al [31] (30%) to economically justify a process of sludge reduction furthermore above the results of Sievers et al [50] on full scale application who reached 20-35% and 19% after aerobic or anaerobic stabilisation and ozone treatment of 0.05 gO 3 gTSS −1 . Deleris et al [51] obtained comparable results (70% of reduction of sludge production) with lower ozone dose (ozonation on the recycling loop 0.05 gO 3 gVSS −1 ).…”
Section: Sludge Reduction Under Aerobic Conditionssupporting
confidence: 83%
“…When sludge heating is to be performed in order to reduce sludge production, sludge solubilisation process would be necessary. For this purpose, two main temperature brackets are to be considered (from economic or efficiency point of view): temperatures either higher or lower than 150 • C [31]. The necessary temperatures to obtain solubilised sludge would be around 160-200 • C [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Paul et al (2006) [17] also reported that thermal treatment promotes cell lysis because extracellular polymeric substances (EPS) such as proteins, lipids and polysaccharides were released. Frølund et al…”
Section: Strain Sweep Testmentioning
confidence: 99%